Analysis and Diminution of NoSQL Injection attacks - Patil, Pritesh; Gaikwad, Ashwini; Badekar, Rachana; Urade, Ankita; Hirve, Rutuja (IJRDO -Journal of Computer Science Engineering, 2017)
Scalability and ease of use has been one of the major reasons behind the popularity ofNoSQL storage systems. Flexibility and scalability of NoSQL databases are major cause foradoption and popularity. Unfortunately, they lack the security measures and awareness thatare required for data protection. The global exposure of these applications makes them proneto the attacks because of presence of vulnerabilities. These security vulnerabilities continueto infect the web applications through injection attacks thus enabling the attackers to attackon the database by injecting malicious code into the statements passed to the databasebecause the new data models and query formats of NoSQL data which in turn makes theattack divergent.